Reducing ammonia loss from urea and improving soil exchangeable ammonium and available nitrate in non waterlogged soils through mixing zeolite and sago (Metroxylon sagu) waste water. - Omar, Latifah; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2011)
Ammonia loss from urea significantly reduces urea-N use efficiency. The objective of this study was to determine the effect of mixing urea with zeolite and sago (Metroxylon sagu) waste water on ammonia volatilization, soil exchangeable ammonium and available nitrate compared with urea alone. The mixtures significantly reduced ammonia loss by 22 to 41% compared with urea alone (straight urea, 46% N). All the mixtures of zeolite and sago waste water with urea significantly increased soil exchangeable ammonium by (39 to 49 ppm) and available nitrate by (0.23 to 2.06 ppm). The mixtures also temporarily reduced soil pH. The temporary reduction of soil pH may have retarded urea hydrolysis. It could be possible to improve the efficiency of urea-N applied to high value crops by addition of zeolite and sago waste water.